Left ventricular function during exercise in trained pre-adolescent soccer players - Unnithan, V. B.; Rowland, T. W.; George, K.; Lord, R.; Oxborough, D. (Scandinavian Journal of Medicine & Science in Sports, 2018)
It is unclear, what the underlying cardiovascular mechanisms are that give rise to the high level of aerobic fitness seen in youth soccer players. The aim of the study was to evaluate global and regional markers of systolic and diastolic function in a group of pre-adolescent soccer players during an incremental exercise test. Twenty-two, male soccer players (SP) from two professional soccer clubs (age: 12.0 ± 0.3 years) volunteered for the study. Fifteen recreationally active boys (CON), of similar age (age: 11.7 ± 0.2 years) were also recruited. All boys underwent a cycle ergometer test to exhaustion. Cardiac dimensions were determined using M-mode echocardiography. During submaximal and maximal exercise, continuous-wave Doppler ultrasound techniques were used to derive stroke volume (SVIndex). Tissue-Doppler imaging was used to quantify systolic (S'adj) and diastolic function (E; E'adj and E/E`) at rest and both submaximal and maximal exercise intensities. Speckle tracking echocardiography was used to determine peak longitudinal e at submaximal exercise intensities. SP demonstrated significantly (P = 0.05) greater peak VO2 values than CON (SP: 48.0 ± 5.0 vs CON: 40.1 ± 7.5 mL·kg-1 ·min-1). Allometrically scaled to body surface area left ventricular end-diastolic volume (LVEDV) was larger (P = 0.05) in the SP (51.3 ± 9.0) compared to CON (44.6 ± 5.8 mL·BSA1.5). At the same relative, submaximal exercise intensities, the SP demonstrated greater SVIndex, cardiac output (QIndex) and E. No differences were noted for peak longitudinal e during submaximal exercise. Factors that augment pre-load and LV volume appear to determine the superior aerobic fitness seen in the soccer players.